The Impact of Learning Environment, Age, Gender, and Duration of Clinical Rotation to Quality of Life of Medical Students - Pamungkasari, E P; ., Hartono; Hastami, Y; Randita, A B T; Apriliani, A K (KnE Life Sciences, 2019)
Medical students in the clinical clerkship face a tight schedule and burden task that can cause ”burn out”. If neglected, it will decline their quality of life. With a good quality of life, a doctor will be able to handle patients optimally. The aim of this study was to determine how the learning environment, age, gender and length of clinical rotation affected the quality of life of medical students in the clerkship stage. An analytic observational study with a cross-sectional approach was conducted at the main teaching hospital in Surakarta, Indonesia. The population was medical students in the clerkship stage. 178 subjects were carried out by cluster sampling. The learning environment was assessed with PHEEM questionnaire and the quality of life was evaluated with WHOQOL BREF questionnaire. The results of data analysis using multiple linear regression showed that each increment in a score of the learning environment would improve the quality of life by 0.13, which is statistically significant (p=0.002). Age, gender, and clinical rotation duration did not significantly (p=0,056; p=0.174; p=0.087) impact the quality of life. The learning environment, age, gender and clinical rotation duration together affect the quality of life of the clinical clerkship stage students by 7.8%. The conclusion is that the learning environment influences the quality of life.